2005
DOI: 10.2486/indhealth.43.413
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Backrest and Torso Twist on the Apparent Mass of the Seated Body Exposed to Vertical Vibration

Abstract: Occupational exposure to whole-body vibration is often combined with a requirement to perform twisting actions. This paper reports a study where the effect of twisting on the biomechanical response of the seated person was investigated. Twelve male subjects were exposed to vertical random whole-body vibration at 0.4 m/s 2 r.m.s. Each subject sat in four different postures: 'back-on', 'backoff', 'twist' (where subjects were required to twist the torso by 90°) and 'move' (where subjects were required to performi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…Since the only input in the frequency range of interest is the one provided by the stimulus and that a non-linear model does not increase the coherence value, the non-linearity is reasonably caused by the variation of the modal parameters in time. This is consistent with what was evidenced in Mansfield and Maeda (2005), where the authors investigated the APMS of seated subjects in case of repeated movements of the upper body: subjects twisted their torso to the left and right with accompanied arm movements. In this situation, the coherence was lower than that derived for the static posture; it was hypothesised that the twisting motion was responsible of the whole drop-off in the coherence function at low frequencies.…”
Section: Coherence Functionsupporting
confidence: 84%
“…Since the only input in the frequency range of interest is the one provided by the stimulus and that a non-linear model does not increase the coherence value, the non-linearity is reasonably caused by the variation of the modal parameters in time. This is consistent with what was evidenced in Mansfield and Maeda (2005), where the authors investigated the APMS of seated subjects in case of repeated movements of the upper body: subjects twisted their torso to the left and right with accompanied arm movements. In this situation, the coherence was lower than that derived for the static posture; it was hypothesised that the twisting motion was responsible of the whole drop-off in the coherence function at low frequencies.…”
Section: Coherence Functionsupporting
confidence: 84%
“…The frequency of the peak reduces with increases in vibration magnitude (Fairley and Griffin, 1989;Holmlund et al, 2000;Mansfield and Griffin, 2000;Smith, 1994), and can be affected by the seated posture (Wang et al, 2004), but not by twisting (Mansfield and Maeda, 2005). In the fore-and-aft (x-) direction the first peak in apparent mass occurs at about 4 Hz if there is backrest contact, but the first peak occurs at about 0.7 Hz if there is no backrest contact (Fairley and Griffin, 1990;Mandapuram et al, 2005).…”
Section: Introductionmentioning
confidence: 96%
“…Among the objective measures, the power absorbed 7,14) , the apparent mass 15) , and the transmissibility 16) have shown encouraging and consistent correlations with the subjective discomfort measures. However, recent studies 17,18) have shown the incapability of the apparent mass to capture the peak in the discomfort when the subjects move, such as twisting their torsos or lifting their arms, at the same time. Maeda et al 18) showed that the peak in the apparent mass was reduced and even diminished in some cases.…”
Section: Introductionmentioning
confidence: 99%